Rethinking modernity - Gupta Santosh; Kar Prafulla C; Mukherji Parul Dave (Delhi Pencraft International, 2005)
This volume is the second in the series that the Forum on Contemporary Theory has brought out as part of its continued effort to ensure that some of the papers presented at its conferences appear in print so that the dialogue on topics of contemporary re
Forum on Contemporary Theory. Conference (6th : 2003 : Jaipur, India)
Keywords: India; Modernity; Social change